Early Pleistocene calcareous nannofossil assemblages from the Gulf of Cadiz reveal glacial-interglacial and millennial-scale variability - Samanta Trotta; Maria Marino; Antje Helga Luise Voelker; Teresa Rodrigues; Patrizia Maiorano; Jos??-Abel Flores; Angela Girone; Marina Addante; Barbara Balestra (Palaeogeography, Palaeoclimatology, Palaeoecology, 2022)
Coccolithophore high resolution (300 years) quantitative analyses have been carried out on Early Pleistocene sediment samples from Integrated Ocean Drilling Program Site U1387 retrieved in the Gulf of Cadiz. The studied interval is well constrained by the delta 18O chronological frame and covers marine isotope stage (MIS) 48 to MIS 45, from 1465.9 ka to 1389.9 ka. The aim is to investigate paleoenvironmental changes during a poorly known interval of the "41 ky world" and understand how climate dynamics controlled coccolithophore abundance and variation at orbital up to millennial scale. Assemblage composition variation and Principal Component Analysis (PCA) indicate that temperature and nutrient availability are the main factors influencing coccolithophores. Precession forcing combined with hydrological and atmospheric dynamics affect changes in coccolithophore assemblage composition and abundance highlighting glacial-interglacial cycles and a millennial scale variability, which is more evident during glacials than during interglacials. Interglacial MIS 47 onset is more abrupt than MIS 45 inception in relation to a more prominent insolation maximum, which favors the sharp increase and highest abundance of warm water taxa in the early MIS 47. Short-term abundance peaks of C. pelagicus spp. pelagicus during glacials document polar-subpolar melting water influx into the Gulf of Cadiz and southward migration of the subpolar front during episodes of high volume ice-sheet in the north hemisphere and reduced Atlantic Meridional Overturning circulation. In late MIS 48 the lowest coccolithophore productivity, induced by colder and stratified surface waters, a terminal stadial has been inferred. Enhanced short-term glacial productivity is favored by higher mixing and nutrient content in surface water due to the strengthened westerly winds during symbolscript phases. This promotes arid condition and upwelling along the studied site. The interglacial short-term coccolithophore productivity increases are associated with ...